2002
DOI: 10.1038/sj.ejcn.1601293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ingestion of virgin olive oil on human low-density lipoprotein composition

Abstract: Objective: To measure the incorporation of oleic acid and antioxidants (phenols and vitamin E) to low density lipoprotein (LDL) after acute and short-term ingestion of virgin olive oil. To study whether this incorporation contributes to an increase in LDL resistance to oxidation. Setting: Department of Food and Nutrition, University of Barcelona, Spain and Department of Lipids and Cardiovascular Epidemiology, IMIM, Barcelona, Spain. Subjects: Sixteen healthy volunteers aged 25 -65 y. Design and interventions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 41 publications
6
59
0
5
Order By: Relevance
“…Both compounds were recovered in all of the fractions, except in the very low density lipoproteins one; concentrations peaked between 1 and 2 h. Covas et al (2006) demonstrated that the postprandial oxidative stress can be modulated by the olive oil phenolic content and that the degree of LDL oxidation decreases in a dose-dependent manner with the phenol concentration of the olive oil ingested. They arrived to these conclusions administering a single dose of olive oil, but similar results were obtained in studies using sustained doses; olive oil consumption for 1 week led to an increase in the total phenolic content of LDL (Gimeno et al, 2002). In a later study, volunteers were requested to ingest virgin, common or refined olive oil daily for 3 weeks (Gimeno et al, 2007).…”
Section: Binding Of Olive Oil Polyphenols To Lipoproteinsmentioning
confidence: 55%
“…Both compounds were recovered in all of the fractions, except in the very low density lipoproteins one; concentrations peaked between 1 and 2 h. Covas et al (2006) demonstrated that the postprandial oxidative stress can be modulated by the olive oil phenolic content and that the degree of LDL oxidation decreases in a dose-dependent manner with the phenol concentration of the olive oil ingested. They arrived to these conclusions administering a single dose of olive oil, but similar results were obtained in studies using sustained doses; olive oil consumption for 1 week led to an increase in the total phenolic content of LDL (Gimeno et al, 2002). In a later study, volunteers were requested to ingest virgin, common or refined olive oil daily for 3 weeks (Gimeno et al, 2007).…”
Section: Binding Of Olive Oil Polyphenols To Lipoproteinsmentioning
confidence: 55%
“…The consumption of vegetables has been related to a protective effect against the aforementioned chronic diseases. The regular consumption of olive oil in the diet has been related to an improvement in the lipoprotein blood profile and protection against oxidation (Gimeno et al, 2002). On the one hand, the consumption of red meat has been related to chronic diseases such as type 2 diabetes mellitus (Schulze et al, 2003b) and some types of cancer (Biesalski, 2002) but, on the other, we must not forget that meat contains such essential micronutrients as vitamin B 12 and is an important dietary source of micronutrients that have been associated with a lower risk of cancer, such as selenium and zinc (Biesalski, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This reduction may be related to growing evidence demonstrating the powerful antioxidant properties of olive oil phenolics both in vitro and in vivo (25). In healthy men, ingestion of virgin olive oil increases the incorporation of oleic acid, phenols and vitamin E into low-density lipoprotein (LDL), which increases LDL resistance to oxidation (26). Olive oil phenol hydroxytyrosol reduces H 2 O 2 generation, H 2 O 2 -induced DNA damage and mRNA levels of GPx in oxidative stress-sensitive human prostate cells (27).…”
Section: Discussionmentioning
confidence: 99%